2020
DOI: 10.33899/ijvs.2019.125646.1120
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and histopathological study of avian influenza virus-H5 (AIV-H5) in broiler farms

Abstract: This study was conducted for diagnosis and description of the pathological changes of AIV-H5 as the causative pathogen in Iraqi broiler farms. The current study was carried out on 84 broiler farms. Infected birds were tested for detection of the AIV infection from the tracheal swabs by rapid chromatographic AIV type A and H5 test kits. In RRT-PCR 8 samples (8 farms) of Trachea were selected to be tested by this assay. Samples of trachea, lung, and spleen from the dead birds with natural AIV-H5 infection were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
4
2
0
Order By: Relevance
“…Pneumonic areas with intense aggregation of leukocytes and vasculitis of the pulmonary blood vessels were also detected in lung. These present histopathological findings are consistent with several previous pathological data reported with HPAI in the literature [ 42 , 44 , 48 , 51 , 52 , 53 ]. In these previous studies [ 42 , 44 , 48 , 51 , 52 , 53 ], trachea and lungs showed congestion, edema, thrombosis, diffuse hemorrhages, necrosis, and sloughing of the epithelial lining of trachea and bronchi, extensive alveolar damage, together with inflammatory cells infiltration including macrophages, lymphocytes, and heterophils.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Pneumonic areas with intense aggregation of leukocytes and vasculitis of the pulmonary blood vessels were also detected in lung. These present histopathological findings are consistent with several previous pathological data reported with HPAI in the literature [ 42 , 44 , 48 , 51 , 52 , 53 ]. In these previous studies [ 42 , 44 , 48 , 51 , 52 , 53 ], trachea and lungs showed congestion, edema, thrombosis, diffuse hemorrhages, necrosis, and sloughing of the epithelial lining of trachea and bronchi, extensive alveolar damage, together with inflammatory cells infiltration including macrophages, lymphocytes, and heterophils.…”
Section: Discussionsupporting
confidence: 93%
“…These present histopathological findings are consistent with several previous pathological data reported with HPAI in the literature [ 42 , 44 , 48 , 51 , 52 , 53 ]. In these previous studies [ 42 , 44 , 48 , 51 , 52 , 53 ], trachea and lungs showed congestion, edema, thrombosis, diffuse hemorrhages, necrosis, and sloughing of the epithelial lining of trachea and bronchi, extensive alveolar damage, together with inflammatory cells infiltration including macrophages, lymphocytes, and heterophils. In addition, depletion of the lymphoid follicles and heterophilic cells infiltration was observed in the spleen, together with hemorrhagic foci and necrosis of the periellipsoid lymphocyte sheaths, which is consistent with several previous studies [ 43 , 48 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefor recognizing vp7gene (glycoprotein) according to its function in infection and pathogenesis as outer capsid protein for neutralization antibody and enter to host cell in replication cycle (21). While (22,23) showed RT-PCR less efficiency than RT-qPCR for amplification in comparison with +ve and -ve control. The present study was designed to explore the role of group A rotavirus as causative agents of diarrhea by using PCR assay as more sensitive technique, in Basrah and Karbala provinces.…”
Section: Prevalence Of Rotavirus In Human Stool Samples By Polymerasementioning
confidence: 99%